Uji Anti Inflamasi Kombinasi Ekstrak Rimpang Kencur (Kaempferia Galanga L.) dan Daun Salam (Syzygium Polyanthum) pada Tikus Putih Galur Sprague Dawley yang Diinduksi Karagenan - Elis Wildayani; Deya Adiby Nabillah; Syilvi Adini (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Inflammation is the body's response to tissue injury, which is usually caused by physical trauma, harmful chemicals, or microorganisms. Kencur rhizomes and bay leaves have been proven effective as anti-inflammatories. The purpose of this study is to determine the anti-inflammatory effect of a combination of kencur rhizome extract and bay leaves in reducing the volume of 1% carrageenan-induced rat foot edema. The research method is a laboratory experiment using 24 Wistar Sprague dawley male white rats with 1% carrageenan induction. The test materials used were KNR (1% carrageenan), KNT (CMC-Na 0,5%), KD1 (50 : 50 mg/kg BB), KD2 (150 : 250 mg/kg BB), KD3 (250 : 75 mg/kg BB), and KPT (diclofenac sodium) ( mg/kg BB). The test materials were administered orally one hour before induction with 0.2 mL of 1% carrageenan. Foot volume measurements were taken every hour for six hours after carrageenan induction. The results showed that the 150 : 250 mg/kg dose combination group could inhibit the onset of inflammation by 89%; the 250 : 75 mg/kg dose combination group could inhibit it by 75%; and the 50 : 50 mg/kg dose combination group could inhibit it by 56%. In the positive control group (diclofenac sodium), the percentage of inflammation inhibition was 60%. Therefore, it can be concluded that the higher the concentration of kencur rhizome extract and bay leaves, the greater the decrease in anti-inflammatory activity. The combination of kencur rhizome extract and bay leaves at a dose of 150 : 250 mg/kgBB is an effective dose for inhibiting edema, as evidenced by the results of this study.